Polymer-modified bitumen using ethylene terpolymers - Keyf, S.; Ismail, O.; Corbacioglu, B. D. (TAYLOR & FRANCIS INC, 2007)
Polymer modified bitumen (PMB) is used in various construction applications, especially in motorways. The aim of this study is to improve features of 60/70 penetration grade, modified bitumen used on highways. Increasing the sensitivity to temperature and oxidation resistance are very important points for the modified bitumen. This condition was provided by reacting the carboxylic acid groups in asphaltene with the reactive ethylene terpolymer to form ester. Reactive ethylene terpolymer ( RETP) and ethylene terpolymer ( ETP) manufactured by DuPont USA were used as additives in this study. Infrared Spectrophotometer ( IR) graphics and optical pictures of the modified bitumen have been examined. It has been observed that the softening point has increased on the other hand, the penetration and ductility values have decreased according to the test results.
Keywords: ductility; penetration; polymer modified bitumens; reactive terpolymer; softening point; RHEOLOGICAL EVALUATION; ASPHALT BINDERS; POLYETHYLENE; COPOLYMERS; BLENDS; Energy & Fuels; Engineering